2022
DOI: 10.1186/s40323-022-00233-9
|View full text |Cite
|
Sign up to set email alerts
|

A deformation-dependent coupled Lagrangian/semi-Lagrangian meshfree hydromechanical formulation for landslide modeling

Abstract: The numerical modelling of natural disasters such as landslides presents several challenges for conventional mesh-based methods such as the finite element method (FEM) due to the presence of numerically challenging phenomena such as severe material deformation and fragmentation. In contrast, meshfree methods such as the reproducing kernel particle method (RKPM) possess unique features conducive to modelling extreme events such as the absence of a structured mesh and the ease of adaptive refinement, among other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…To address the aforementioned issue concerning the failure of the VC correction under material fragmentation, we propose a VC and Non-VC blending strategy based on local deformation intensity. This method draws inspiration from the blending approach utilized in the Lagrangian/semi-Lagrangian reproducing kernel particle method discussed by Baek et al [44] and Pasetto et al [42], where the blending is employed to reduce computational costs when employing semi-Lagrangian methods for material fragmentations.…”
Section: Vc and Non-vc Blending Schemementioning
confidence: 99%
“…To address the aforementioned issue concerning the failure of the VC correction under material fragmentation, we propose a VC and Non-VC blending strategy based on local deformation intensity. This method draws inspiration from the blending approach utilized in the Lagrangian/semi-Lagrangian reproducing kernel particle method discussed by Baek et al [44] and Pasetto et al [42], where the blending is employed to reduce computational costs when employing semi-Lagrangian methods for material fragmentations.…”
Section: Vc and Non-vc Blending Schemementioning
confidence: 99%
“…The load transfer method is widely used in traditional pile settlement and axial force calculations, and its basic idea is to divide the pile into several elastic units, each of which is connected to the soil body by a nonlinear spring, which is used to simulate the load transfer relationship between the pile and the soil [15]. In addition, some scholars have analyzed the influence of the discretization used on the results obtained, and found that the way in which discretization is performed can affect results [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…To more effectively deal with the extreme deformation in geomaterials, the semi-Lagrangian meshfree formulation has been elaborated by Guan et al (2009), Kwok et al (2015) and Mahdavi et al (2020). More recently, a deformation dependent coupled Lagrangian/semi-Lagrangian meshfree formulation was proposed by Baek et al (2022) to more effectively carry out the landslide modeling.…”
Section: Introductionmentioning
confidence: 99%
“…(2020). More recently, a deformation dependent coupled Lagrangian/semi-Lagrangian meshfree formulation was proposed by Baek et al. (2022) to more effectively carry out the landslide modeling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation